Biografi Alinur: Seorang Penggiat Tradisi Lisan Rambai Kota Pariaman (2000-2022) - Saputra, Randi Alamsyah; Salam, M. Abdul (AHKAM, 2024)
This study discusses the issue of Alinur's biography as an oral tradition activist in Rambai village, Pariaman city in the period 2000-2022. The oral tradition that is the object of this study is pasambahan. Pasambahan being one of the oral cultures in Minangkabau, especially in Pariaman City, must be well preserved so that it is not lost by time. Alanur, one of the pasambahan activists who comes from Rambai village, Pariaman city, has a very strong determination in teaching pasambahan with the aim that the younger generation can know the pasambahan well. The problem that arises today is the reduced interest in learning the younger generation in learning pasambahan and the difficulty of finding teachers who teach pasambahan well. This study aims to explain the background of Alinur emerging as a pasambahan teacher and analyze Alinur's work in inheritance and preservation of local pasambahan culture. In this study the author uses the History method which consists of four stages consisting of heuristics, source criticism, interpretation, and, historiography. The results in this study explain that Alinur lives in Rambai village with a simple life. He has studied in Surau since childhood and he has gained various knowledge such as learning religion, silat, until he learned pasambahan. At first, he participated in pasambahan learning only because of the request of his father who wanted Alinur to know the customs in his area. However, over time he felt interested and began to seriously learn pasambahan. He studied with a variety of different teachers over a short period of time. After he was good at pasambahan, he began to participate in activities related to pasambahan outside the region. Eventually, Alinur feels that this material is very important to be inherited because it is part of the local culture so he teaches people regardless of age and never charges fees. Alinur is now well known to many with his intelligence and he also has students who are even outside the West Sumatra area.